Low cross reactivity between wild type and deamidated AAV can lead to false negative results in immune monitoring T-cell assays - Bing, So Jin; Warrington, Stephanee; Mazor, Ronit (Frontiers in Immunology, 2023)
During gene therapy trials, immune responses against adeno-associated virus (AAV) vectors are monitored by antibody assays that detect the humoral and T-cell mediated cellular responses to AAV vectors. T cell assays commonly utilize the collection of patients’ peripheral blood mononuclear cells (PBMCs) and stimulation with AAV-derived overlapping peptides. We recently described that spontaneous deamidation coincides with T cell epitopes in AAV capsids and that spontaneous deamidation may enhance or decrease immunogenicity in some individuals. This raised the concern for false negative results of antibody detection and PBMC immune monitoring assays because these assays use wild-type (WT) AAV or WT peptides for T cell re-stimulation and these peptides may not re-activate T cells that were stimulated with deamidated AAV capsid. To investigate this concern, we modeled the scenario by expanding T cells with deamidated peptides and evaluated the cross-reactivity of expanded T cells to WT peptides. In the majority of samples, cells that were expanded with deamidated peptides and restimulated with WT peptide had significantly lowered IL-2 and IFN-γ production. Spiking the four deamidated peptides to the WT peptide pool used for re-stimulation, restored the signal and corrected the performance of the assay. We also evaluated the impact of deamidation on anti AAV binding antibodies and did not observe a major impact on seroprevalence detection of AAV9. These data indicate that a high level of deamidation in AAV therapy may result in underestimation or even failure to detect immune responses against WT peptides during cellular immune monitoring.